If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + -3) + 16 = 2(x + 5) Reorder the terms: 3(-3 + x) + 16 = 2(x + 5) (-3 * 3 + x * 3) + 16 = 2(x + 5) (-9 + 3x) + 16 = 2(x + 5) Reorder the terms: -9 + 16 + 3x = 2(x + 5) Combine like terms: -9 + 16 = 7 7 + 3x = 2(x + 5) Reorder the terms: 7 + 3x = 2(5 + x) 7 + 3x = (5 * 2 + x * 2) 7 + 3x = (10 + 2x) Solving 7 + 3x = 10 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 7 + 3x + -2x = 10 + 2x + -2x Combine like terms: 3x + -2x = 1x 7 + 1x = 10 + 2x + -2x Combine like terms: 2x + -2x = 0 7 + 1x = 10 + 0 7 + 1x = 10 Add '-7' to each side of the equation. 7 + -7 + 1x = 10 + -7 Combine like terms: 7 + -7 = 0 0 + 1x = 10 + -7 1x = 10 + -7 Combine like terms: 10 + -7 = 3 1x = 3 Divide each side by '1'. x = 3 Simplifying x = 3
| 6x+6= | | 10x+2+4x+7=13x+3 | | 12y-9=16y+19 | | 9x-3=3+8x | | 7x+3y=16 | | 23-6x=-61 | | v(4v-24)=-6 | | -8y+5=-9y+3 | | h^2+26h-10=0 | | -6y+4=7y+5 | | 27x+13x=73 | | 3x^2-3x+5=0 | | 5p+5=7-4p | | x-2x+5=5 | | X^2+11x+13=0 | | (3x+7)(x+1)=10 | | 9-41= | | x^2-30x+125=0 | | 2x(x+8)+15=0 | | g^2-8g+11=0 | | 2x-5y=1 | | 5(x+6)=8+5x | | 3x^2+2x+8=0 | | d^2+22d+121=18 | | 8x+3y=8 | | 9x^10=4x^9+41 | | b^2-8b+17=7 | | 15x^2=3x+7 | | 4p+3=10+3p | | 4p+3=10+3 | | 7x+2y=2 | | 4x+16-18=-8x+2 |